Metal-insulator transitions in pressed pellets of BF4 - doped poly(3-methylthiophene) - Pawlicka, A.; Pereira, E. C.; Nascimento, O. R.; Bulhões, L. O. S.; Walmsley, L. [UNESP] (Taylor & Francis, 1997)
From Electron Spin Resonance (ESR) data in pressed pellets of BF4 - doped Poly(3-methylthiophene) (P3MT) we obtained simultaneously the paramagnetic susceptibility and. the microwave conductivity. We observed a transition from a high-temperature insulator state to a room-temperature metallic state. Around 240K. evidence of a Peierls transition is observed, but if the sample is slowly cooled, this transition is partially suppressed. DC conductivity data taken with the sample quenched to 79 K show a non-linear I-V response for very small electric fields, suggesting depinning of Charge-Density Wave (CDW). The data for heating and cooling the system above room temperature, indicate the formation of bipolarons.
Keywords: Charge-density waves; Conducting polymers; Electron spin resonance; Metal-insulator transitions; Aromatic compounds; Boron compounds; Conductive plastics; Electric conductivity of solids; Electron spin resonance spectroscopy; Microwave conductivity; Paramagnetic susceptibility; Peierls transition; Phase transitions